Redesign of Nablus Specialist Hospital - Hassoun, Hayat; Khalil, Raghad; Surakji, Yasmeen (My University, 2018)
Post occupancy evaluation of Nablus specialist hospital (case study). The importance of this project is to identify the deficiencies of Nablus specialist hospital evaluation then analyze and solve it, in order to increase comfort, safety and aesthetic level of the building. This project will include many aspects to be analyzed such as structural, architectural, electrical, mechanical and environmental. The main objective of this project is to improve the performance level of the building. By modifying architectural deficiencies that appear in the function and relations between zones and areas, also control the horizontal and vertical circulation. Analyze the lighting aspect of the building such as the utilization of day light in addition to the distribution of artificial lighting. Developing the acoustic through increasing the sound insulation. Improve heating, cooling also ventilation system. In this project the process should contain qualitative and quantitative data that should be collected from walkthrough. The data will be evaluated with manual equipments then compare with standards and codes. According to these data questionnaire should be developed and distributed to collect the respondents’ satisfaction regarding the performance of different aspects by using statistical software such as (spss). Then evaluate and check the building by using a software programs such as auto cad, sap, rivet, dialux evo and design builder. Post occupancy evaluation (POE) method is adopted in this project.